Optimalisasi LAZISNU Dalam Pengelolaan Dana ZIS (Studi Kasus di LAZISNU Liprak Kidul Kab Probolinggo) - Reza Hilmy Luayyin; Muhammad Nabat Ardli; Saifur Rizal (Wasīlah: Journal Of Sharia Sciences, 2025)
This study aims to analyze the optimization of zakat, infaq, and sadaqah (ZIS) management at LazisNu Liprak Kidul, Probolinggo Regency, by examining the implementation of four management functions: planning, organizing, actuating, and controlling. Using a qualitative approach with a case study design, data were collected through in-depth interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that although LazisNu Liprak Kidul has implemented the four management functions, their application remains suboptimal. The planning function lacks measurable targets and does not include a structured evaluation mechanism. The organizing function is constrained by limited competent human resources and the absence of clear job descriptions. Program implementation is still ad-hoc, not data-driven, and not integrated with the institution’s strategic plan. The controlling function focuses mainly on financial reporting, with insufficient attention to sharia compliance and operational efficiency. This study concludes that improving managerial capacity is essential, including developing SMART-based strategic planning, strengthening organizational structure, enhancing human resource skills, integrating data into program implementation, and adopting more comprehensive monitoring mechanisms. These improvements are expected to enhance effectiveness, transparency, and social impact in the management of ZIS at the community level. The study contributes to the advancement of community-based zakat governance. Keywords : Optimization, Management, ZIS,